MiRNA expression profiling and emergence of new prognostic signature for oral squamous cell carcinoma - Christo Rajan (Nature Portfolio, 2021)
Abstract Oral squamous cell carcinoma (OSCC), the most common type of head and neck cancers, is associated with high recurrence, metastasis, low long-term survival rates and poor treatment outcome. As deregulated miRNA expression plays a crucial role in malignant transformation and cancer progression, the present study is aimed at profiling the miRNA expression pattern in OSCC and developing a new miRNA prognostic signature for oral cancer. MiRNA expression profiling was performed using MiRNA microarray in 30 tumor and 18 normal samples. MiRNA signature obtained was validated with quantitative real time PCR (qRT-PCR) in 144 tumor and 36 normal samples. The potential targets, clinical implications and prognostic value of the miRNA signature were elucidated by various bioinformatics and statistical analyses. Microarray profiling identified a set of 105 miRNAs to be differentially expressed in OSCC, out of which a subset of 19 most dysregulated miRNAs were validated by qRT-PCR. In silico analysis revealed the signature miRNAs to be involved in various cancer associated pathways. Up-regulation of miR-196a, miR-21, miR-1237 and downregulation of miR-204, miR-144 was associated with poor prognosis of OSCC patients. The mir-196a/miR-204 expression ratio emerged as best predictor for disease recurrence and patient survival. Altogether, our study identified a miRNA signature for OSCC with prognostic significance.